2018
DOI: 10.1101/380758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting transcriptomic signatures of neuronal differentiation and maturation using iPSCs

Abstract: Human induced pluripotent stem cells (hiPSCs) are a powerful model of neural differentiation and maturation. We present a hiPSC transcriptomics resource on corticogenesis from 5 iPSC donor and 13 subclonal lines across nine time points over 5 broad conditions: self-renewal, early neuronal differentiation, neural precursor cells (NPCs), assembled rosettes, and differentiated neuronal cells that were validated using electrophysiology. We identified widespread changes in the expression of individual transcript fe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Previously, it was reported that hiPSCs acquire a prevalent glycolytic state compared to differentiated fibroblasts ( 39 ). Although characterization of neural development in hiPSCs has been widely explored using genome-wide profiling and biochemical analysis ( 55 57 ), there is very little research conducted focusing on the changes related to cellular metabolism, and none of them were performed at the single-cell level with a quantitative measure ( 58 ). Our study demonstrates that SCRM is able to provide semiquantitative glycogen content in situ at the single-cell level ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that hiPSCs acquire a prevalent glycolytic state compared to differentiated fibroblasts ( 39 ). Although characterization of neural development in hiPSCs has been widely explored using genome-wide profiling and biochemical analysis ( 55 57 ), there is very little research conducted focusing on the changes related to cellular metabolism, and none of them were performed at the single-cell level with a quantitative measure ( 58 ). Our study demonstrates that SCRM is able to provide semiquantitative glycogen content in situ at the single-cell level ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, comprehensive RNA expression profiling of human brain tissues from early embryonic to late adult postmortem stages has shown that neuronal cells produced from iPSCs closely recapitulate the progression from early embryogenesis to late fetal periods in vitro and yield neuronal cells of various stages of maturity [61,62,63,64,65,66]. Immature neurons and networks express molecules and processes that are not operative in the adult and follow a crucial developmental sequence that is instrumental in the formation of functional entities.…”
Section: Ipscs Provide Unique Access To Early Neurodevelopment In mentioning
confidence: 99%
“…While recent work has extended the number of cell populations that can be isolated by antibodies to separate neurons into their excitatory and inhibitory subclasses and oligodendrocytes from other glia 12 , there are likely very few additional cell types that are possible to isolate using nuclear antibodies for DNAm samples. Researchers have therefore turned to using cell type-specific RNA microarray and sequencing datasets to adapt these reference-based deconvolution algorithms to homogenate RNA-seq samples 7,[13][14][15][16][17][18][19][20][21][22][23] . The majority of these studies have focused on tissues other than the brain, which can be freshly obtained and dissociated into individual cells for single cell RNA-seq (scRNA-seq) or be sorted into specific cell populations using flow cytometry for cell type-specific expression profiling.…”
Section: Introductionmentioning
confidence: 99%